High Complete Response Rate in Patients With Metastatic Renal Cell Carcinoma Receiving Autologous Cytokine-Induced Killer Cell Therapy Plus Anti-Programmed Death-1 Agent: A Single-Center Study - Zhao, Lingdi; Li, Tiepeng; Song, Yongping; Yang, Yonghao; Ma, Baozhen; Zhang, Yong; Shang, Yiman; Xu, Benling; Guo, Jindong; Qin, Peng; Han, Lu; Fu, Xiaomin; et al. (Frontiers in Immunology, 2022)
Background and Objective The results of the CheckMate 025 trial established the status of nivolumab in the second-line treatment of metastatic renal cell carcinoma (mRCC), with an objective response rate (ORR) of 25% and a complete response (CR) rate of 1%. Thus, the efficacy of anti-programmed death (PD)-1 antibodies in the second-line treatment of mRCC requires improvement. The purpose of this study was to explore the clinical efficacy and safety of anti-PD-1 agents combined with cytokine-induced killer (CIK) cell therapy for refractory mRCC. Patients and Methods Patients with mRCC refractory to previous targeted therapy were included in this study. All patients received anti-PD-1 plus CIK cell therapy. The ORR and CR rate, progression-free survival (PFS), overall survival (OS), and safety were assessed. Results CR was observed in seven of the 29 patients, and partial response was observed in five patients. The ORR was 41.4% and the median PFS was 15.0 months. Up to the last follow-up, 15 patients died with an average survival time of 37 months. Among the patients who achieved a CR, one experienced cerebellar metastasis 18.8 months after discontinuation, but achieved CR again after localized gamma knife and 1-month axitinib treatment. This regimen was tolerated well and there was no treatment-related death. Conclusions Combination therapy with anti-PD-1 and CIK cell therapy is safe and effective in patients with mRCC refractory to previous targeted therapy. The high CR rate and long disease-free survival even after long-term discontinued therapy suggest that this combination treatment may represent a potential curative regimen for this type of malignancy.